REBRANDING HALAL – TOURISM PADA MASYARAKAT SEKITAR DESTINASI WISATA TIMUR INODONESIA DENGAN PLATFORM MEDIA SOSIAL DIGITAL - SYAIFUDDIN, M. IRFAN; HAKIM, PRATIWI RAHMAH (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of this research is to find out the understanding, skills and marketing methods of the community around halal tourism tourist destinations. Providing skills in using digital social media in rebranding and marketing halal tourism for communities around Eastern Indonesia destinations. The service activities are carried out using the Asset Based Community Development (ABCD) approach, which prioritises the utilisation of assets and potential around the target community. The location of the service is in the Labuan Bajo tourism community. The implementation of training with Focus Group Discussion (FGD) which involved representatives of 20 tourism businesses in Labuan Bajo. The achievement obtained from this training is the opening of insights into the importance of halal labels in tourism businesses. The community can create digital content through Instagram as a means of promotion. ABSTRAKTujuan dari pengabdian ini adalah mengetahui pemahaman, keterampilan dan cara pemasaran masyarakat sekitar destinasi wisata pariwisata halal. Memberikan bekal keterampilan menggunakan media sosial digital dalam rebranding dan marketing pariwisata halal untuk masyarakat sekitar destinasi Indonesia Timur. Kegiatan pengabadian dilaksanakan menggunakan pendekatan Asset Based Community Development (ABCD), yang mengutamakan pemanfaatan asset dan potensi yang ada di sekitar masyarakat sasaran. Lokasi pengabdian adalah pada masyarakat wisata Labuan Bajo. Pelaksanaan pelatihan dengan Focus Group Discussion (FGD) dimana melibatkan perwakilan 20 pelaku usaha pariwisata di Labuan Bajo. Capaian yang didapat dari pelatihan ini adalah terbukanya wawasan pentingnya label halal dalam usaha pariwisata. Masyarakat dapat membuat konten digital melalui instagram sebagai sarana promosi.